Evaluation Of Marine Economic Literature Usability Website Using Heuristic Method - Sufadlan Nugraha; Putri Ivana Anggraeni M (Journal of Intelligent Decision Support System (IDSS), 2022)
In the current era of globalization, all fields are experiencing advances in information technology, including the marine and fisheries aspects. One of the results obtained from this progress is the presence of a website suhana.web.id which is engaged in marine economic literacy, but in its use the website apparently still has several shortcomings such as content updates that are not carried out optimally and regularly. Seeing these problems, the researcher aims to conduct an evaluation on the website by using the heuristic evaluation method in order to provide recommendations. In applying the heuristic method, the author involves three evaluators who are experts in the field of web programming and interface design. The results of the calculation of several problems in this evaluation are the high level of problems found in the Aesthetic and Minimalist Design aspects with a figure of 38%.